2013
DOI: 10.1159/000357474
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in the Primary Auditory Cortex of Postlingually Deaf Patients: An FDG-PET Study

Abstract: Background/Purpose: Previous FDG-PET studies have indicated neuroplasticity in the adult auditory cortex in cases of postlingual deafness. In the mature brain, auditory deprivation decreased neuronal activity in primary auditory and auditory-related cortices. In order to reevaluate these issues, we used statistical analytic software, namely a three-dimensional stereotaxic region of interest template (3DSRT), in addition to statistical parametric mapping (SPM; Institute of Neurology, University College of Londo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
4
5
0
Order By: Relevance
“…These findings could further reinforce the relative cerebral glucose metabolism (rCGM) or blood flow decrease found in the auditory cortex and in many associative areas in previous studies on patients with chronic deafness and tinnitus (Okuda et al, 2013;Ueyama et al, 2015;Lanting et al, 2009), suggesting that reorganizational behaviour also occurs during ISSNHL. One hierarchical organization of primary and associative auditory cortex (Ruytjens et al, 2006) involves carrying out demanding neural computations, performed automatically and efficiently by the normal brain.…”
Section: Metabolic Decrease In Auditory and Associative Areassupporting
confidence: 86%
“…These findings could further reinforce the relative cerebral glucose metabolism (rCGM) or blood flow decrease found in the auditory cortex and in many associative areas in previous studies on patients with chronic deafness and tinnitus (Okuda et al, 2013;Ueyama et al, 2015;Lanting et al, 2009), suggesting that reorganizational behaviour also occurs during ISSNHL. One hierarchical organization of primary and associative auditory cortex (Ruytjens et al, 2006) involves carrying out demanding neural computations, performed automatically and efficiently by the normal brain.…”
Section: Metabolic Decrease In Auditory and Associative Areassupporting
confidence: 86%
“…If deprived sound input activates fewer excitatory fibers, the activities of excitatory and inhibitory neurons can become unbalanced and, as a result, the neuronal response in one hemisphere will be reduced compared to the other ( Fan et al, 2015 ). This finding is consistent with the previous studies in patients with chronic deafness or tinnitus reporting reduced blood flow in the AC ( Lanting et al, 2009 ; Okuda et al, 2013 ; Micarelli et al, 2017 ). However, some recent studies reported no significant difference in the ReHo value between the ISSNHL patients and the healthy controls in any brain region.…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al (2001) reported hypoperfusion in the primary cortex and auditory-association cortex of prelingually deaf patients; the hypoperfusion was positively correlated with degree of hearing improvement after cochlear implantation. Prior PET reports from subject with postlingual deafness ( n = 7) (Okuda et al, 2013) and idiopathic sudden SNHL patients ( n = 14) (Micarelli et al, 2017) indicated lower glucose metabolism in the temporal lobe and insula attributed to the absence of sensory input. The difference between our insula results and these earlier reports may be related to the types of hearing loss (i.e., unilateral vs. bilateral, genetic factors), duration of deafness, small sample size, and other factors such as cognitive and emotional differences as illustrated by worse scores on SDMT, SAS, and HAMD in our SNHL subjects.…”
Section: Discussionmentioning
confidence: 99%